Catechin Bioavailability Following Consumption of a Green Tea Extract Confection Is Reduced in Obese Persons without Affecting Gut Microbial-Derived Valerolactones - Geoffrey Y. Sasaki; Yael Vodovotz; Zhongtang Yu; Richard S. Bruno (MDPI AG, 2022)
Obesity-related cardiometabolic disorders are driven by inflammation, oxidative stress, and gut dysbiosis. Green tea catechins protect against cardiometabolic disorders by anti-inflammatory, antioxidant, and prebiotic activities. However, whether obesity alters catechin bioavailability remains unknown. We hypothesized that obesity would decrease catechin bioavailability due to altered gut microbiota composition. Obese and healthy persons completed a pharmacokinetics trial in which a confection formulated with green tea extract (GTE; 58% epigallocatechin gallate, 17% epigallocatechin, 8% epicatechin, 6% epicatechin gallate) was ingested before collecting plasma and urine at timed intervals for up to 24 h. Stool samples were collected prior to confection ingestion. Catechins and γ-valerolactones were assessed by LC-MS. Obesity reduced plasma area under the curve (AUC0-12h) by 24-27% and maximum plasma concentrations by 18-36% for all catechins. Plasma AUC0-12h for 5'-(3',4'-dihydroxyphenyl)-γ-valerolactone and 5'-(3',4',5'-trihydroxyphenyl)-γ-valerolactone, as well as total urinary elimination of all catechins and valerolactones, were unaffected. ⍺-Diversity in obese persons was lower, while Slackia was the only catechin-metabolizing bacteria that was altered by obesity. Ascorbic acid and diversity metrics were correlated with catechin/valerolactone bioavailability. These findings indicate that obesity reduces catechin bioavailability without affecting valerolactone generation, urinary catechin elimination, or substantially altered gut microbiota populations, suggesting a gut-level mechanism that limits catechin absorption.